E-Waste Facility Locator using Integrated Map Interface - R., Sathyabama A; S., Abdul Afshith; K., Vidya Sagar (Journal of Ubiquitous Computing and Communication Technologies, 2024)
The E-Waste (Electronic Waste) Facility Locator application utilizes the user’s current location to help find a nearby e-waste disposal center. The application features a user-friendly map interface that allows the user to select an e-waste facility based on their preferences. The user can either go to the facility to dispose of the e-waste or request the facility to pick up the waste at their doorstep. The entire system is managed by a system admin. Overall, the E-waste Facility Locator app helps users dispose of electronic waste responsibly, reducing pollution and conserving resources.